The Authority Of Bank Indonesia In Issuing Legal Products According To The State Auxillary Agencies Theory - Saifulloh, Putra Perdana Ahmad; Azheri, Busyra (Pascasarjana Ilmu Hukum, Universitas Widya Gama Malang, 2023)
As an State Auxillary Agencies. Bank Indonesia is authorized to make it’s own legal products that bind the public. Currently the product of he regulation is in a Bank Indonesia Regulation, as a consequence of one of the characteristics of an State Auxillary Agencies namely a self regulatory body. From this study it may be concluded that Bank Indonesia only has the authority to enforce the delegation’s regulation. Second, Bank Indonesia, in the hierarchy of regulations, should be in line with Presidential Regulations. Third, the Governor of Bank Indonesia may make State Administative Decisions in accordance with his authority. Fourth, the stages of formation of Bank Indonesia Regulations in the Bank Indonesia Regulation concerning the establishment of Regulations at Bank Indonesia, include: a.planning; b.arrangement; c.discussion; d.determination; e.promulgation; and f.dissemination. Fifth, the establishment of a Bank Indonesia Regulation in order to prioritize meaningful public participation in the process of its information, especially to involve academics. For this reason, according to the author, academics need to be empowered by Bank Indonesia in the establishment of Bank Indonesia in the Framework of improving the State Auxillary Agencies.